2018
DOI: 10.14260/jemds/2018/306
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Calcium, Magnesium, Uric Acid and Liver Enzymes in Pregnancy Induced Hypertension

Abstract: BACKGROUND The lowering of serum calcium can cause an elevation of blood pressure in pre-eclamptic mothers. Magnesium is a potent vasodilator of uterine and mesenteric arteries and aorta. Magnesium also increases NO production causing vasodilation. Elevation of uric acid in preeclampsia is due to factors such as abnormal renal clearance, increased tissue breakdown, acidosis and a rise in the activity of the xanthine oxidase/ dehydrogenase enzyme. In preeclampsia hypervascularisation and vasoconstriction of liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Other studies have suggested a reduced vitamin K 2 level could be associated with insulin resistance and damage to the kidney and liver [51][52][53]. On the other hand, PIH patients had a significantly higher level of UA, GGT and INS in our study, which indicated the possibility of kidney and liver damage and metabolic abnormalities, and these alterations were found to be associated with PIH [54][55][56][57]. It is consistent that the changes of these indicators and functional modules, suggesting that they might interact with each other to participate in the occurrence of PIH.…”
Section: Exploration Of the Potential Mechanisms Of The Gut Microbiomesupporting
confidence: 49%
“…Other studies have suggested a reduced vitamin K 2 level could be associated with insulin resistance and damage to the kidney and liver [51][52][53]. On the other hand, PIH patients had a significantly higher level of UA, GGT and INS in our study, which indicated the possibility of kidney and liver damage and metabolic abnormalities, and these alterations were found to be associated with PIH [54][55][56][57]. It is consistent that the changes of these indicators and functional modules, suggesting that they might interact with each other to participate in the occurrence of PIH.…”
Section: Exploration Of the Potential Mechanisms Of The Gut Microbiomesupporting
confidence: 49%